Implementation of Drug Information Services at Colomadu II and Jaten II Health Centers, Karanganyar Regency - Sudarwati, Vivid Latri; Peranginangin, Jason Merari; Antoro, Sutopo Edy (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
Drug Information Service (DIS) is an activity provided by pharmacists to patients. However, some aspects of DIS are often not implemented, resulting in non-compliance and failure of therapy in patients. Health center pharmacists often do not explain to patients about the side effects, interactions and contraindications of drugs. This study aims to determine the implementation of drug information services in health care facilities in two health centers in Karanganyar Regency, namely Colomadu II and Jaten II Health Centers. This study is a cross-sectional study conducted in July and August 2023 at two health centers in Karanganyar Regency, Indonesia, namely Colomadu II and Jaten II Health Centers. This study used a survey questionnaire given to patients seeking treatment at Colomadu II and Jaten II Health Centers. This study involved a total of 50 participants, with the same number of respondents from both Colomadu II and Jaten II Health Centers. The results of this study indicate that the DIS given to patients at the Health Center, in six aspects of information, namely name, preparation, dosage, use, storage, drug indications have been (100%) conveyed, but four of the ten indicators, namely contraindications, stability, side effects, and drug interactions have not been provided optimally (below 100%). that there is no significant difference in the two health centers in each variable because the p value 0.05. Based on the results of statistical analysis, it was found that there was no significant difference in the implementation of Drug Information Services between Colomadu II and Jaten II Health Centers in the implementation of PIO drug storage (p = 1.00), drug contraindications (p = 0.556), drug stability (p = 0.728), drug side effects (p = 0.222), and drug interactions (p = 0.095). This needs to be a concern for Pharmacists and pharmacy staff at the Health Center to support the safety of drug use and successful treatment.